- #1

- 8

- 0

Let f(x,y)= -2x^2-2xy+y^2+2 Use Lagrange multipliers to find the minimum of f subject to the constraint 4x-y = 6

∂F / ∂x =.....................

i got -4x-2y+2y but i coming out as wrong what am i missing

∂F/ ∂Y= ................

The function f achieves its minimum, subject to the given constraint, where

x =

y =

λ=

f =

thank you

∂F / ∂x =.....................

i got -4x-2y+2y but i coming out as wrong what am i missing

∂F/ ∂Y= ................

The function f achieves its minimum, subject to the given constraint, where

x =

y =

λ=

f =

thank you

Last edited: